Energy metabolism disorder dictates chronic hypoxia damage in heart defect with tetralogy of fallot - Liu, Libao; Huang, Lei; Yao, Lishuai; Zou, Fan; He, Jinyuan; Zhao, Xiaodong; Mei, Lugang; Huang, Shuai (Frontiers in Cardiovascular Medicine, 2023)
Background Tetralogy of Fallot (TOF) belongs to cyanotic heart damage, which is the most common in clinic. In the chronic myocardial hypoxia injury related to TOF, the potential molecular mechanism of cardiac energy metabolism remains unclear. Materials and methods In our study, microarray transcriptome analysis and metabonomics methods were used to explore the energy metabolism pathway during chronic hypoxia injury. The gene expression omnibus (GEO) dataset GSE132176 was obtained for analyzing the metabolic pathways. The clinical samples (right atrial tissues) of atrial septal defect (ASD) and TOF were analyzed by metabonomics. Next, we screened important pathways and important differential metabolites related to energy metabolism to explore the pathogenesis of TOF. Results Gene set enrichment analysis (GSEA) indicated that fructose 6-phosphate metabolic process, triglyceride metabolic process, and et al. were significantly enriched. Gene set variation analysis (GSVA) results showed that significant difference of ASD group and TOF group existed in terpenoid metabolic process and positive regulation of triglyceride metabolic process. Pathways with significant enrichment (impact > 0.1) in TOF were caffeine metabolism (impact = 0.69), sphingolipid metabolism (impact = 0.46), glycerophospholipid metabolism (impact = 0.26), tryptophan metabolism (impact = 0.24), galactose metabolism (impact = 0.11). Pathways with significant enrichment (impact > 0.1) in ASD are caffeine metabolism (impact = 0.69), riboflavin metabolism (impact = 0.5), alanine, aspartate and glutamate metabolism (impact = 0.35), histidine metabolism (impact = 0.34) and et al. Conclusion Disturbed energy metabolism occurs in patients with TOF or ASD, and further investigation was needed to further clarify mechanism.